Backstepping approach for the control of the double-fed asynchronous generator in a wind power system - Chahboun, Mbarek; Abouyaakoub, Mohcine; Ali, Ali Ait; El Mrabet, Aziz; Hihi, Hicham; Ouabi, Hassan; El Bid, Youssef (Institute of Advanced Engineering and Science, 2025)
This paper aims to model and control the dual-fed asynchronous generator (DFIG). The modeling and vector control were simulated using MATLAB, followed by the application of the Backstepping control strategy. A comparative study between two DFIG control strategies, fuzzy logic control (FLC) and Back-stepping control, was conducted. The results for the Backstepping approach are discussed and compared with FLC, highlighting that the Backstepping technique addresses robustness issues regarding variations in operating conditions and internal parameters. Both control strategies are applied to a wind turbine system, and the simulation results and robustness tests are analyzed.